The Sp1-Responsive microRNA-15b Negatively Regulates Rhabdovirus-Triggered Innate Immune Responses in Lower Vertebrates by Targeting TBK1 - Chang, Renjie; Chu, Qing; Zheng, Weiwei; Zhang, Lei; Xu, Tianjun (Frontiers in Immunology, 2021)
Viral infection induces type I interferon (IFN) production, which plays pivotal roles in host innate antiviral responses. However, excessive production of type I IFN disrupts immune homeostasis and further may induce autoimmune and inflammatory diseases. Therefore, researches on the regulatory mechanisms underlying type I IFN production are of great interest. In this study, we report that a Sp1–responsive miR-15b plays a negative role in siniperca chuatsi rhabdovirus (SCRV)-triggered antiviral response in teleost fish. We found that SCRV could significantly upregulate the expression of miiuy croaker miR-15b. Enhanced miR-15b negatively regulates SCRV-triggered type I IFN and inflammatory cytokine production by targeting TANK-binding kinase 1 (TBK1), thereby promoting viral replication. Importantly, we found that miR-15b feedback regulates antiviral innate immune response through NF-κB and IRF3 signaling pathways. The collective findings suggest that miR-15b plays a regulatory role in virus–host interactions, which outlines a new regulation mechanism of fish’s innate immune responses.